Hormone Therapy and Replacement in Cancer and Aging-related Diseases - Rangel, Leticia B. A.; Kirubamani, Hephzibah; Victor Silva, Ian; Cilas Morais Lyra Junior, Paulo (IntechOpen, 2020)
This edited volume, Hormone Therapy and Replacement in Cancer and Aging-related Diseases, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of hormone replacement therapy. The book comprises single chapters authored by various researchers and edited by experts active in the hormone replacement therapy research area. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on hormone replacement therapy, and opens new possible research paths for further novel developments.